2016
DOI: 10.1039/c5cp06858d
|View full text |Cite
|
Sign up to set email alerts
|

Physical insights into salicylic acid release from poly(anhydrides)

Abstract: Salicylic acid (SA) based biodegradable polyanhydrides (PAHs) are of great interest for drug delivery in a variety of diseases and disorders owing to the multi-utility of SA. There is a need for the design of SA-based PAHs for tunable drug release, optimized for the treatment of different diseases. In this study, we devised a simple strategy for tuning the release properties and erosion kinetics of a family of PAHs. PAHs incorporating SA were derived from related aliphatic diacids, varying only in the chain le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
(34 reference statements)
0
2
0
Order By: Relevance
“…Poly­(anhydride-ester) based polyactives can also be employed as prodrug platforms for the controlled release of various therapeutics and bioactive small organic molecules including antioxidants, anti-inflammatory drugs, , antiseptics, , antibiotics, and antimicrobial drugs . Recently, Madras et al also reported several poly­(anhydride-esters) that contained bioactive molecules such as salicylic acid and aspirin in the polymer main chain. They studied the release kinetics associated with the hydrolytic degradation of the polymer matrix and subsequently investigated their anti-inflammatory and antibacterial activities.…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Poly­(anhydride-ester) based polyactives can also be employed as prodrug platforms for the controlled release of various therapeutics and bioactive small organic molecules including antioxidants, anti-inflammatory drugs, , antiseptics, , antibiotics, and antimicrobial drugs . Recently, Madras et al also reported several poly­(anhydride-esters) that contained bioactive molecules such as salicylic acid and aspirin in the polymer main chain. They studied the release kinetics associated with the hydrolytic degradation of the polymer matrix and subsequently investigated their anti-inflammatory and antibacterial activities.…”
Section: Applicationsmentioning
confidence: 99%
“… 186 Recently, Madras et al also reported several poly(anhydride-esters) that contained bioactive molecules such as salicylic acid and aspirin in the polymer main chain. 187 190 They studied the release kinetics associated with the hydrolytic degradation of the polymer matrix and subsequently investigated their anti-inflammatory and antibacterial activities.…”
Section: Applicationsmentioning
confidence: 99%